Hubungan Keharmonisan Keluarga dan Konsep Diri dengan Kenakalan Remaja - Sudarmo, Priyo, Dr. Nanik Prihartanti, M.Si (2016)
Lately, the behavior of juvenile delinquency increasingly varies, and it shows unlawful behavior. Delinquency is not only shown by brawl, but already leads to violating the law and moral. The study aims to demonstrate empirically the correlation between family harmony and self-concept to juvenile delinquency in a vocational school in the city of Semarang. The subjects were students of sex males-SMK aged between 16-18 years old. The population in this study were 1200 with samples of 300 students were taken through a proportional random technique of class X, XI, and XII. Data collector used a scale of juvenile delinquency, family harmony scale, and self-concept scale. Technical analysis used multiple linear regressions. Results: (1) There was a correlation between family harmony and self-concept to juvenile delinquency with effective contribution of 0.748 or 74.8%. (2) There was a correlation between family harmony with juvenile delinquency, and the effective contribution is 48.3%. (3) There was a self-concept and juvenile delinquency correlation, and the effective contribution is 26.5%.